-5(2+3)+3z=

Simple and best practice solution for -5(2+3)+3z= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(2+3)+3z= equation:


Simplifying
-5(2 + 3) + 3z = 0

Combine like terms: 2 + 3 = 5
-5(5) + 3z = 0

Multiply -5 * 5
-25 + 3z = 0

Solving
-25 + 3z = 0

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '25' to each side of the equation.
-25 + 25 + 3z = 0 + 25

Combine like terms: -25 + 25 = 0
0 + 3z = 0 + 25
3z = 0 + 25

Combine like terms: 0 + 25 = 25
3z = 25

Divide each side by '3'.
z = 8.333333333

Simplifying
z = 8.333333333

See similar equations:

| 5(y+4)=6(y-4) | | x^2+X^2=1 | | 5x+2x=2x-10 | | y^2+11y=12 | | 3y+30=-y+14 | | 3y+30=-y+13 | | 6m+2m+3=11 | | h+2(h-1)+3=22 | | x+238y=2379 | | 6p+2(2p+3)=16 | | -9=6h+2h+7 | | x+(2x-1)+(3x-4)=27 | | 9x-49=0 | | 4ln(5x)=8 | | 2m^2+16m+30=0 | | 11=k+4 | | -2(6t+8)= | | 5x+8=5x+7 | | 5z-2=3z+5 | | 20-8x+30-8x=180 | | (X+5)-(4x-1)=0 | | 9-x+3x-2-9x= | | 15a=-5a+10 | | 4*(X-2)=4+2*(X-1) | | 6m=24+x | | 140s*20s= | | 6+2y+y=12 | | 8m-3m=15 | | 8x^2+5y^2=40 | | 2x+37=8x+7 | | 8x-12=4x+20 | | x=y^2-5 |

Equations solver categories